HIV replication is associated to inflammasomes activation, IL-1, IL-18 and caspase-1 expression in GALT and peripheral blood (2018)
Background Human immunodeficiency virus (HIV) promotes an inflammatory process, leading to the progressive loss of the functional capacity of the immune system. The HIV infection induces alterations in several tissues, but mainly in the gut-associated lymphoid tissue (GALT). However, the degree of GALT deterioration varies among infected individuals. In fact, it has been shown that HIV-controllers, who spontaneously control viral replication, exhibit a lower inflammatory response, and a relative normal frequency and function of most of the immune cells. Inflammasomes are molecular complexes involved in the inflammatory response, being NLRP1, NLRP3, NLRC4, AIM2 and Pyrin inflammasomes, the best characterized so far. These complexes regulate the maturation of cytokines of the IL-1 family, including IL-1β and IL-18. These cytokines have been associated with immune activation and expansion of HIV target cells, promoting viral replication. Interesting, some reports indicate that HIV induces the activation of the NLRP3 inflammasome, but the role of this, and other inflammasomes during HIV infection, especially in GALT, remains unclear. Objective To compare the relative expression of inflammasome components and the proinflammatory response related to their activity, between HIV-progressors and HIV-controllers.Methods GALT biopsies and peripheral blood mononuclear cells (PBMCs) from 15 HIV-controllers and 15 HIV-progressors were obtained. The relative expression of the following inflammasome components were evaluated by RT-PCR: NLRP3, NLRC4, NLRP1, AIM2, ASC, Caspase-1, IL-1β and IL-18. In addition, plasma concentration of IL-18 was evaluated as an indicator of baseline proinflammatory status. Finally, in supernatants of PBMCs in vitro stimulated with inflammasome agonists, the concentrations of IL-1β and IL-18 were quantified by ELISA. Results HIV-progressors exhibited higher expression of IL-1β, IL-18 and caspase-1 genes in GALT and PBMCs compared with HIV-controllers. In addition, HIV-progressors had also increased expression of ASC in PBMCs. When plasma levels were evaluated, IL-18 was increased in HIV-progressors. Interesting, these patients also showed an increased production of IL-1β in supernatants of PBMCs stimulated in vitro with the agonists of AIM2, NLRP1 and NLRC4 inflammasomes. Finally, the expression of caspase-1, NLRP1, IL-1β and IL-18 in GALT or peripheral blood was correlated with CD4+ T-cell count and viral load. Conclusion Our results suggest that during HIV-infection, the required signals to induce the expression of different components of the inflammasomes are produced, both in GALT and in periphery. The activation of these molecular complexes could increase the number of target cells, favoring HIV replication and cell death, promoting the disease progression.